Pengaruh Pengungkapan Corporate Social Responsibility dan Mekanisme Good Corporate Governance Terhadap Tax Avoidance - Diamonalisa Sofianty; Lina Herlina (Universitas Islam Bandung, 2020)
This study aims to examine the effect of disclosure of corporate social responsibility and the mechanism of Good Corporate Governance on tax avoidance. This research uses descriptive verification method with a quantitative approach. The data collection technique used is documentation. The population chosen in this study are manufacturing companies in various industrial sectors and the food and beverage sub-sector consumption sector which are listed on the Indonesia Stock Exchange (BEI). Sampling was done using purposive sampling method, in order to obtain a sample of 18 companies that meet the criteria. The test results show that the disclosure of corporate social responsibility has an effect on tax avoidance, while the good corporate governance mechanism has no effect on tax avoidance. This research can contribute as a reference for parties related to taxation, namely when reducing tax avoidance cases, it also takes pressure to pressure companies so that companies are willing to increase CSR disclosure. Furthermore, this research can also contribute to regulators in determining policies related to Standard Operating Procedures that must be carried out properly by members of the organizational structure that form a GCG mechanism so that the GCG mechanism within the company can influence tax avoidance activities.